STUDY OF THE INTERACTION BETWEEN GENETIC AND ENVIRONMENTAL FACTORS IN THE PATHOPHYSIOLOGY OF ANXIETY - Kasimova Iroda Khusan kizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
The aim of this study is to analyze the pathophysiological mechanisms underlying anxiety disorders, taking into account neurobiological, genetic, and environmental factors. The main objectives include investigating the interaction of various body systems in the development of anxiety, identifying key gaps in current knowledge, and developing recommendations to improve diagnosis and treatment.